MANAJEMEN KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI GURU DI MTSN 2 KOTA MAKASSAR - Zulkifly, Ahmad; Ismail Tolla; Wahira (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the principal's management in improving teacher competence at MTsN 2 Makassar City. In addition, the study seeks to identify the supporting and inhibiting factors in the implementation of efforts to enhance teacher competence, as well as to explore the principal's role in designing and implementing teacher competence improvement programs at MTsN 2 Makassar City. This research employs a qualitative method with a descriptive approach. This approach was chosen because the study aims to describe and understand in depth the phenomenon of the principal's management in enhancing teacher competence at MTsN 2 Makassar City. The qualitative method allows data to be gathered from the participants’ perspectives, thus providing a clear picture of the principal's role in teacher competence development. The results of the study indicate that the principal's management in improving teacher competence at MTsN 2 Makassar City is carried out through academic qualification enhancement, continuous training, regular supervision, as well as motivation and reward systems. The principal actively encourages teachers to participate in both internal and external training, monitors their progress, and aligns teaching with technological advancements and student needs. The supporting factors in improving teacher competence include appropriate academic qualifications, institutional support through training and supervision, and teachers’ motivation for professional growth. The inhibiting factors involve mismatches between educational background and subjects taught, limited access to external training, and challenges in adapting to technology. However, institutional support, supervision, and internal motivation help overcome these obstacles. The principal’s role in enhancing teacher competence is strategic and comprehensive, covering training, supervision, reward systems, and periodic evaluations. This approach leads to improved teacher competence, which positively affects teaching quality and student achievement.